Sugarcane Aphid Resistance in Pearl Millet - D. D. Serba; J. P. Michaud (Kansas Agricultural Experiment Station Research Reports, 2019)
Sugarcane aphid, (Melanaphis sacchari(Zehntner) (Hemiptera: Aphididae)) has become an important pest of sorghum in the US. This recent invasion is assumed to be either as a result of a host shift from sugarcane in the south or introduction of a specialized strain from tropical Africa. If host shift happened through adaptive change to infest sorghum, other closely related species such as pearl millet are in danger from this voracious pest. The resistance level of pearl millet genotypes representing A-, B-, R-lines and germplasm were evaluated under climate-controlled growth chamber along with resistant and susceptible sorghum hybrids. Ten plants of the genotypes were planted in a row in a tray per replicate. Cuttings infested with a stock colony of aphids maintained on the susceptible sorghum line were evenly distributed across the soil in each tray to ascend the plants at will. The damage was scored two times (5 and 8 days after infestation) using a scale of 1 to 9 (1 = no visible damage, 9 = dead). The statistical analysis of data found that there are significant differences among genotypes for aphid feeding damage. However, none of the pearl millet genotypes were affected to the level of susceptible sorghum. Four genotypes of pearl millet had resistance levels similar to the resistant sorghum. No statistical differences were observed among the A, B, and R-lines and the germplasm—implying that the cytoplasmic male-sterility system, nuclear restorer gene, and sterility maintainer counterparts have no impact on SCA resistance and susceptibility in pearl millet.
Keywords: pearl millet; sugarcane aphid; Melanaphis sacchari; tolerance